UNVEILING THE JOURNEY: EXPLORING THE PERSONAL EXPERIENCE OF NOVICE EFL TEACHER IN THE CLASSROOM - Ferawaty Syam; Herman Resyadi; Ary Putra Sanusi (International Journal of Research on English Teaching and Applied Linguistics, 2023)
This research aims the personal experiences of novice English as a Foreign Language (EFL) teachers in the classroom. The objective is to gain insights into the challenges faced by novice EFL teachers and strategies to address challenges. Descriptive method is employed, focusing on a single participant selected through purposive sampling. Data is collected through semi-structured interviews. Thematic analysis is used to analyze the interview data. The findings reveal that novice EFL teachers h challenges related to classroom management, lesson planning, and student engagement. Limited teaching experience and a lack of pedagogical knowledge are also identified as contributing factors. However, he demonstrate resilience and engage various strategies to overcome the challenges by seeking mentorship, engaging in professional development, and utilizing student-centered approaches. This research contributes to the existing literature on novice teacher experiences and informs stakeholders to held teacher training programs in the EFL context.